Analysis of worker posture of Make-Up Artist by Standard Nordic Questionnaire method and Rapid Entire Assessment - Asda, Cut Lirma Saputri; Hasanuddin, Iskandar; Husni, Husni; Firsa, Teuku (Politeknik Negeri Lhokseumawe, 2024)
Working posture is one of the factors that can influence work productivity because working with an abnormal posture can cause ergonomic problems, especially muscle injuries in workers. This research aims to analyze the worker posture of Make-up Artists (MUA) in Meukek District, South Aceh Regency. The analysis was carried out using the (SNQ) method to identify musculoskeletal complaints and (REBA) with the help of Ergo fellow software to assess worker posture. The research results showed that as many as 80% of MUA workers experienced complaints of musculoskeletal, with the most frequent complaints in the waist, shoulders, and neck. The work posture score of MUA workers is categorized as high risk (REBA score 11) in several activities, such as when cleaning the face and applying eyelashes. Risk factors that cause unergonomic work postures include long work duration (2-3 hours per client), with dynamic body positions. Lack of ergonomic work facilities. Based on the research results, several solutions are recommended to improve MUA work posture, including providing solutions for good body posture when working and designing ergonomic work chairs so that they can help MUA maintain optimal body posture while working and reduce risk musculoskeletal. By having work chairs that suit the design, it is hoped that it can improve the comfort and health of MUA workers and reduce the complaints they have been experiencing.